Strategies for exploiting listening tasks in Campaign 2 at English Department, Military Science Academy = Chiến lược khai thác các bài nghe trong giáo trình Campaign 2 tại khoa tiếng Anh, Học viện Khoa học Quân sự. M.A Thesis Linguistics: 60 14 10 - Nguyễn, Thị Thanh Huệ (ĐHNN, 2017)
M.A. Thesis. English Methodology -- University of Foreign Languages and International Studies. Vietnam National University, Hanoi, 2010